Karakteristik sosial-ekonomi dan Preferensi Hunian berdasar Tipe Status Hak Tempat Tinggal Keluarga Berpenghasilan Rendah di Kawasan Industri Kecamatan Ungaran Timur, Kabupaten Semarang - Muhammad Farhan Ahsani; Asnawi Asnawi (Jurusan Perencanaan Wilayah dan Kota, 2022)
: Low income people do not have enough opportunities to access adequate housing in proper quality standard. They do not have many options for renting or buying affordable housing in the city due to financial constraints. Especially for low-income families (MBR) who already have a family, housing is increasingly needed because of their increasing activity. Currently, the government continues to provide housing assistance for MBR in the form of subsidized Mortgage (KPR FLPP), but the demand for housing continues to increase from time to time. Therefore, providing sustainable affordable housing for low-income families has various challenges. This study aims to explain the socio-economic characteristics and housing preferences of low-income families living in the industrial area in Ungaran Timur, Kabupaten Semarang. The research is located in East Ungaran Subdistrict, Semarang Regency as a representation of the mediumsized city area in Central Java Province. In the research location, five type of housing occupancy status found in the area: one unit of low-cost flat (the Ungaran Rusunawa Gedang Anak) and 4 typologies of landed houses categorized by rights statuses: home ownership rights, rental houses in installments(leasing), and rental landed houses. The research method used is quantitative by using a questionnaire to 100 MBR families(respondents). Identification of socio-economic characteristics using descriptive methods and cross tabulation, identification of physical characteristics of the dwelling using the scoring method with a Likert scale, and identification of occupancy preferences using descriptive methods. Based on the research, it was found that families who can afford homeownership housing have a minimum income of IDR 3,500,000 by working as permanent workers. Most families who work as permanent laborers start buying houses at the age of 30-36 years. Meanwhile, families who work as contract laborers and self-employed workers with an average income of below Rp. 3,500,000 choose to live in rental low-cost flat or rental landed house which is located close to the current workplace. Each dwelling shows different physical characteristics. Owned houses and houses in installments undergo building modifications because of their status as property rights, while flat and leased landed houses do not experience a change in building shape because their occupancy status is rented. The location of rusunawa and landed rental houses shows the distance and or accessibility to workplaces of less than 2 km, while low-income families in privately owned houses and houses in installments need to travel more than 2 km to get to work or about 4 km, some families should have 30 minutes commuting to get to their work. In the selection of new housing, most low-income families showed similar preferences where ownership status, proximity to workplaces, availability of clean water infrastructure and disaster-free locations were priorities.